Development of the conceptual and terminological apparatus of warehousing logistics in the works of Russian and foreign authors - M. Yu. Uchirova; A. N. Larina (Вестник университета)
The main approaches to the basic concepts of warehousing logistics in the works of russian and foreign authors are considered. the peculiarities of understanding the terms “warehouse”, “warehousing”, “warehousing system” are revealed. the main historical stages of the development of warehouses and storage facilities are reflected. based on the information provided, the following key features are highlighted: the warehouse is a complex system with its own interconnections and internal processes; a modern warehouse economy should be formed according to an optimized logistics system, of which it is a part, and be able to adapt to the slightest fluctuations and changes in this system; difficulties arising in the field of building a warehousing system can be solved with the help of a competently and clearly developed warehouse model based on the application of a logistics approach and the development of an adaptive warehouse management algorithm.